ANALYSIS OF THE VISION OF YOGYAKARTA GOVERNOR ABOUT THE INDIAN OCEAN CENTURY: THE REALITY AND NEEDED - Adi Wibawa; Ahmed Varrel Alkahfi Mauza; Resitaka Aulia Nurmamurti; Pramestia Sekar Salsabilla (LPPM Universitas Abdurrab, 2023)
Indonesia, as a maritime country, has many opportunities and threats. It requires greater attention to the sea area. Meanwhile, the Yogyakarta Province which is trying to develop its coastal areas also needs to be implemented in the development of marine infrastructure. This research uses qualitative methods. This article used Geopolitical Theory and Sea Power Theory to conduct the analysis. The data used is primary data in the form of interviews and secondary data obtained from books, journal articles, and online publications. As a result, the Government of Indonesia has issued a policy in the form of a World Maritime Axis. This policy can be the basis for the development of marine management in Indonesia. Meanwhile, the Vision of the Governor of Yogyakarta regarding the Indian Ocean Century must be realized in constructing a new TPI and developing TPI into PPN and PPS to increase productivity and people's welfare. Meanwhile, the collaboration between the community and law enforcement needs to be continued with the support of technology.